Rewitalizacja terenów powojskowych w Polsce - wybrane problemy i przykłady - Obrębalski, Marek (Revitalization of Post-Military Areas in Poland - Selected Problems and Examples, 2006)
The abandoned post-military areas generally originate from political transformations in Europe and the subsequent decrease in demand for military areas and buildings. The necessity of revitalization of post-military areas is perceived not only on local and regional levels, but also on national level. Legnica, Borne Sulinowo, Nysa and Jelenia Góra are the most interesting examples of revitalized post-military areas. Designing and implementation of revitalization strategies were given a new perspective in the National Development Programme between 2004 and 2006 and in the Integrated Operations Programme for Regional Development. Activities targeted at enhancing the restructuring processes of local development through supporting local projects among others related to revitalization of post-military objects and areas are formulated within a priority objective of "Local Development". Obviously this is a great opportunity for local authorities that can be used to enhance socio-economic development and increase the competitiveness of urban areas, interpreted as the ability of individual territorial units to succeed in market competition.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 681-688